KEANEKARAGAMAN JENIS SATWALIAR DI KAWASAN PERKEBUNAN KELAPA SAWIT DAN STATUS PERLINDUNGANNYA: STUDI KASUS KAWASAN UNIT PENGELOLAAN PT. MITRAKARYA AGROINDO, KABUPATEN SERUYAN, KALIMANTAN TENGAH - Arief, Harnios (Media Konservasi, 2016)
Damage or degradation of forests with moderate to severe category had occurred in the region of Mitrakarya Agroindo Ltd  from year 1998 to 2004. The inventory and identification of wildlife species diversity in plantation areas has done in several habitat types that still exist in this area of oil palm companies. From the observation found 25 species of mammals which belong to 17 families, 47 species of birds belonging to the 20 families and 5 species of reptiles. Protected areas of peat swamp forest and secondary forest ecosystem on mineral sois are  important areas for the protection and preservation of endangered species/protected. This is indicated by it was be found 16 species of mammals, 15 species of birds and 2 species of  reptiles of  rare / protected category. Keywords: ecosystem, habitat, wildlife, species, diversity.